Comparison of adjustable male slings and artificial urinary sphincter in the treatment of male urinary incontinence: a retrospective analysis of patient selection and postoperative continence status - Grabbert, Markus Tobias; Nyarangi-Dix, Joanne (World journal of urology, 2019)
Purpose To analyze and compare preoperative patient characteristics and postoperative results in men with stress urinary incontinence (SUI) selected for an adjustable male sling system or an artificial urinary sphincter (AUS) in a large, contemporary, multi-institutional patient cohort.Methods658 male patients who underwent implantation between 2010 and 2012 in 13 participating institutions were included in this study (n = 176 adjustable male sling; n = 482 AUS). Preoperative patient characteristics and postoperative outcomes were analyzed. For statistical analysis, the independent T test and Mann-Whitney U test were used.ResultsPatients undergoing adjustable male sling implantation were less likely to have a neurological disease (4.5% vs. 8.9%, p = 0.021), a history of urethral stricture (21.6% vs. 33.8%, p = 0.024) or a radiation therapy (22.7% vs. 29.9%, p = 0.020) compared to patients that underwent AUS implantation. Mean pad usage per day (6.87 vs. 5.82; p < 0.00) and the ratio of patients with a prior incontinence surgery were higher in patients selected for an AUS implantation (36.7% vs. 22.7%; p < 0.001). At maximum follow-up, patients that underwent an AUS implantation had a significantly lower mean pad usage during daytime (p < 0.001) and nighttime (p = 0.018). Furthermore, the patients’ perception of their continence status was better with a subjective complete dry rate of 57.3% vs. 22.0% (p < 0.001).ConclusionsPatients selected for an AUS implantation showed a more complex prior history and pathogenesis of urinary incontinence as well as a more severe grade of SUI. Postoperative results reflect a better continence status after AUS implantation, favoring the AUS despite the more complicated patient cohort.
Gesehen am 03.04.2020
Published online 2018